Prototipe Sistem Monitoring Penggunaan Daya Listrik Peralatan Elektronik Rumah Tangga Berbasis Internet Of Things - Budi Prayitno; Pritasari Palupiningsih (PETIR, 2019)
Power consumption of PLN customers from household sector is quite large. It comes from the use of household appliances, such as refrigerators, televisions, dispensers, lights and air conditioners. The customers assume that their electricity usage is wasteful, but unfortunately it couldn’t be known in detail which household electrical appliances spend the most electricity. So that, difficult for the customers to monitor the power usage of each household electrical equipments. Regarding to this issue, this research focused on making a prototype of a household electrical power usage monitoring system. This system can be used by PLN customers of households sector to find out which household appliances use large power, so that the customers can manage the use of household appliances. In implementing that monitoring, it needs a capable wattmeter devices to measure the power usage of household electronic equipments The results of this measurement electric current, voltage, and power data measured through sensors. Those measurement data is sent to the database server system monitoring through the internet of things (IoT) device so that monitoring can be done through the system in a real time. This study produced a prototype of household electronic equipments power usage monitoring system based on IoT.